ANALYSIS OF EMPLOYEE PERFORMANCE IN IMPROVING PUBLIC SERVICES AT DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OFFICE OF SORONG REGENCY - Mubalus, Steni Feni Ema; Nur, Syarah (SOSCIED, 2024)
Performance is the fulfillment of official tasks by staff members in order to accomplish a goal in compliance with the policies set forth by the institution. Many people are interested in this public service and people from many walks of life can directly benefit from it. A publically accessible component of the Department of Population and Civil Registration Office government apparatus is the State Civil Apparatus or Aparatur Sipil Negara (ASN). We aim to find out how well the apparatus at the Sorong Regency Population and Civil Registration Service perform. We employed a qualitative descriptive research. Interviews, documentations, and observations were utilized for gathering data. The Head of the Population Registration Services Division and the Head of the General and Personnel Subdivision served as the research's primary informants. Two personnel and two community service users served as supporting informants. To analyze data we employed data reduction, data display, and conclusion drawing method. The findings demonstrate how apparatus performance in delivering public services was evaluated using metrics related to the tangible, reliability, responsiveness, assurance, and empathy dimensions. We discovered that attempts to enhance service quality, specifically by creating a positive impression through these five dimensions, have been demonstrated by the growth in services offered. Nonetheless, there was still a need to raise the standard of service in relation to the five suggested dimensions.